The mathematician Česlovas Masaitis - Kaušylaitė, Giedrė (Lietuvos matematikos rinkinys, 2003)
Professor Česlovas Masaitis is an interwar graduate of Vytautas Magnus University (VDU), a worker in mathematics-nature’s faculty (MGF) of astronomy cathedral, a scientist, granted in the United States of America (the USA), and a character of society, distinguished in miscellaneous foreign Lithuanians’ work. In survey of professor’s scientific and social work we can differentiate four periods of his life, which were spent in different countries (Russian (1914–1921), Lithuanian (1921–1944), German (1944–1949) and USA (since 1949)). Each of them was related with different cultures, which naturally had an influence on the formation of scientist’s character and attitudes. The main task of this article is to present the survey of professor’s mathematical works in Lithuania and the USA.